2004
DOI: 10.1002/hed.10381
|View full text |Cite
|
Sign up to set email alerts
|

Vision enhancement system for detection of oral cavity neoplasia based on autofluorescence

Abstract: Background. Early detection of squamous cell carcinoma (SCC) in the oral cavity can improve survival. It is often difficult to distinguish neoplastic and benign lesions with standard white light illumination. We evaluated whether a technique that capitalizes on an alternative source of contrast, tissue autofluorescence, improves visual examination.Methods. Autofluorescence of freshly resected oral tissue was observed visually and photographed at specific excitation/ emission wavelength combinations optimized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 25 publications
2
75
0
2
Order By: Relevance
“…However, this approach does not completely remove all the abnormal tissue in all individuals. Poh et al and Svistun et al showed that most tumors have occult changes and that the width for subclinical extension ranges between 4 and 25 mm, often extending in at least one direction by over 10 mm with some potentially malignant disorder, thus increasing the chance of tumor recurrence [21,23]. In this study, all surgical margins were clinically normal and had negative results for malignancy, but subclinical alterations showed mild spectral changes confirming the need for further investigation at the molecular level.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, this approach does not completely remove all the abnormal tissue in all individuals. Poh et al and Svistun et al showed that most tumors have occult changes and that the width for subclinical extension ranges between 4 and 25 mm, often extending in at least one direction by over 10 mm with some potentially malignant disorder, thus increasing the chance of tumor recurrence [21,23]. In this study, all surgical margins were clinically normal and had negative results for malignancy, but subclinical alterations showed mild spectral changes confirming the need for further investigation at the molecular level.…”
Section: Discussionsupporting
confidence: 59%
“…For instance, direct fluorescence visualization has been used in different tissues and organs and successfully distinguished premalignant and malignant lesions that cannot be detected by naked eye [22][23][24][25][26]. In our study, spectroscopy satisfactorily discriminated normal tissue and slightly altered mucosa from cancerous lesions.…”
Section: Discussionmentioning
confidence: 55%
“…The measured fluorescence intensity also indicates absorption, particularly from hemoglobin. There has been some success using fluorescence spectroscopy to detect cancer and pre-cancer [1][2][3][4][5]. One of the important issues in the successful implementation of any spectroscopic device is the proper calibration and the control of extraneous variation.…”
Section: 1: the Use Of Spectroscopic Measurementsmentioning
confidence: 99%
“…Optical techniques can quantitatively assess the presence of bound contrast agent noninvasively in near real-time, in contrast to current diagnostic techniques of invasive biopsy and delayed microscopic assessment. The optical signature of the contrast agent could be easily detected and quantified in vivo using spectroscopy, [6][7][8][9][10][11][12] low resolution 2D imaging [13][14][15][16] or high resolution 3D confocal microscopy. [17][18][19][20][21][22][23][24][25] Several studies have previously investigated the use of in vivo fluorescence spectroscopy based on autofluorescence to diagnose malignancy in the oral cavity.…”
mentioning
confidence: 99%
“…The longer excitation wavelength of the fluorescent dye avoids interference from many of the molecules present in tissue that absorb and scatter light at the optimal wavelengths for autofluorescence (300-440 nm). 7,8,[10][11][12][13] Using a dye that fluoresces at a longer wavelength also allows for increased penetration depth. Also, the intensity of fluorescence emitted by the contrast agent is higher than that of endogenous fluorophores, resulting in a stronger optical signal.…”
mentioning
confidence: 99%